Impacts of the COVID-19 pandemic on the Democratic Republic of Congo’s charcoal value chains: the case of Kisangani - Center for International Forestry Research (Center for International Forestry Research, 2021)
The socio-economic effects of the COVID-19 pandemic have been far reaching, impacting regional and local supply of forest products and affecting the livelihoods of millions of people. A recent study by CIFOR-ICRAF conducted in Kisangani – the DRC’s third largest city – and one of its supply basins, the Yangambi landscape, shows both the resilience of the charcoal trade in continuing to supply the urban population with cooking fuel, and the vulnerability of the operators involved in production and trade. Uncertainty and shifting actors in light of COVID-19 restrictions threaten many livelihoods and do not offer an enabling environment for more sustainable practices. Vulnerabilities that have become visible during the pandemic need to be subject of reforms addressing informal trade and “building back better” for a sustainable charcoal sector.